Characteristics and outcome of multiple myeloma patients presenting with anaemia only: A retrospective multi-centre study. (February 2021) - Shragai, Tamir; Gatt, Moshe E.; Shaulov, Adir; Katodritou, Eirini; Triantafyllou, Theodora; Lavi, Noa; Pouli, Anastasia; Sioni, Anastasia; Vaxman, Iuliana; Zektser, Miri; Ganzel, Chezi; Benyamini, Noam; et al.
Highlights: Patients with Multiple myeloma presetting with anaemia only are rare. Anaemia-only MM patients have higher degree of bone marrow plasmacytosis. Anaemia-only MM patients showed lower rates of deep responses to induction therapy. Anaemia-only MM patients represents a unique, potentially less favorable population. Abstract: Background: Multiple myeloma (MM) patients presenting with anaemia as their sole clinical manifestation are rare and not fully defined. Methods: Retrospective multi-site study comparing the characteristics and outcome of MM patients with anaemia only with matched patients, presenting with multi-organ disease. Results: Anaemia-only patients had a higher percentage of bone marrow monoclonal plasma cells group (median 60% [IQR 42−80%] vs. 37% [IQR 17–65%], respectively; p < 0.001), and a lower responsiveness to treatment (≥VGPR rates were 54% vs 74%, p = 0.049). Median survival in anaemia only patients was 65.9 ± 6.9 vs 83.4 ± 8.8 months in matched control patients (P = n.s). Conclusions: MM patients presenting with anaemia only represents a unique, potentially less favorable population.